Prevalence of Keel Bone Damage in Red Jungle Fowls (Gallus gallus)—A Pilot Study - Käthe Elise Kittelsen; Per Jensen; Jens Peter Christensen; Ingrid Toftaker; Randi Oppermann Moe; Guro Vasdal (Animals, 2020)
Keel bone damage (KBD) is a highly prevalent problem in commercial egg production. KBD consists of two different conditions affecting the keel: Keel bone deviation and keel bone fractures (KBF). Deviations are linked to pressure on the keel, e.g., from perching. The causative factors for KBF are not clear; however, selection for efficient egg production has been suggested as a major contributing factor. An important step to shed light on the role of selective breeding as an underlying cause of KBF in modern laying hens is to evaluate the keel bones of the ancestor, the red jungle fowl. To the authors’ knowledge, this has never previously been published. The aim of this study was therefore to describe the prevalence of KBD in a study group of red jungle hens and roosters housed in an aviary system. The present study examined 29 red jungle fowls 112 weeks of age post-mortem; 12 hens and 17 roosters. Keel bones were evaluated by external palpation for deviations and fractures. Palpation was followed by autopsy. No fractures were detected in the 17 roosters; one had a very slight deviation. Of the 12 red jungle hens in this pilot study, one had a single fracture and 10 hens had a very slight deviation.